Internet Memes: Leaflet Propaganda of the Digital Age - Nieubuurt, Joshua Troy (Frontiers in Communication, 2021)
Internet memes are one of the latest evolutions of "leaflet" propaganda and an effective tool in the arsenal of digital persuasion. In the past such items were dropped from planes, now they find their way into social media across multiple platforms and their territory is global. Internet memes can be used to target specific groups to help build and solidify tribal bonds. Due to the ease of creation, and their ability to constantly reaffirm axiomatic tribal ideas, they have become an adroit tool allowing for mass influence across international borders. This text explores the link between internet memes and their ability to "hack" the attention of anyone connected to internet using dense modality and cognitive biases. Furthermore the text discusses Internet meme's ability sew discord by consistently reaffirming preexisting tribal bonds and their relation to traditional PSYOP tactics initially used for analog leaflet propaganda.